UJI POTENSI EKSTRAK ETANOL BAWANG LANANG HITAM (Allium sativum L.) DALAM PENURUNAN KADAR LOGAM BERAT TIMBAL (Pb) SECARA IN VITRO - Anggraini, Devina Ingrid; Febryana, Amanda Alerya (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Black garlic (Allium sativum L.) is a fermented product made from garlic. This fermentation process has an effect on the chemical compound content of black shallots which has increased, especially in polyphenolic compounds, flavonoids and other antioxidant compounds. Flavonoids are compounds that are able to bind metal ions and reduce metal levels because they contain secondary metabolite compounds that have -OH and -O groups. The aim of this research is to determine the potential of black garlic (Allium Sativum L.) to reduce lead (Pb) metal levels. Determination of the reduction potential of black spring onions reacted with 30 ppm Pb metal and various extracts of 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm and 300 ppm which were analyzed using Atomic Absorption Spectrophotometry at a wavelength of 283.3 nm. The results of black garlic extract have the potential to reduce levels of lead metal (Pb) with an EC50 value of 147.96 ppm and a % KV of 0.7296%.